1988
DOI: 10.1002/jmv.1890260108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hepatitis delta virus superinfection on the clearance of hepatitis B virus (HBV) markers in HBV carriers in Japan

Abstract: To elucidate the influence of hepatitis delta virus (HDV) superinfection on the clearance of hepatitis B virus (HBV) associated antigens in HBV carriers, we examined for antibody to hepatitis delta antigen (anti-HD) serial sera collected from 1,029 HBV carriers in Kure, Japan. Of the 242 HBV carriers with hepatitis B e antigen (HBeAg), 28 became seropositive for anti-HD, of whom 18 (64.3%) cleared HBeAg; 214 did not become seropositive for anti-HD, of whom 70 (32.7%) cleared HBeAg. Thus, HBeAg clearance was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Our results are compatible with the published data by (Ichimura et al, 1988). They concluded that, HBeAg clearance was observed in a significantly higher proportion of HDV-superinfected carriers18/28 (64.3%) as compared with carriers without HDV infection 70/214 (32.7%) (P-value < 0.005), suggesting that HDV superinfection can be considered as an inducer factor of HBeAg clearance in HBV carriers.…”
Section: Effect Of Hdv On Hbe Ag and Hbe Absupporting
confidence: 93%
“…Our results are compatible with the published data by (Ichimura et al, 1988). They concluded that, HBeAg clearance was observed in a significantly higher proportion of HDV-superinfected carriers18/28 (64.3%) as compared with carriers without HDV infection 70/214 (32.7%) (P-value < 0.005), suggesting that HDV superinfection can be considered as an inducer factor of HBeAg clearance in HBV carriers.…”
Section: Effect Of Hdv On Hbe Ag and Hbe Absupporting
confidence: 93%
“…In this study, a low HBeAg-positive rate (16.3%) was also found among HBsAg-positive drug abusers than in with other studies in Taiwan Chung et al, 1988;Liu et al, 19841. Some studies [Ichimura et al, 1988;Krogsgaard et al, 19871 indicate that HDV infection plays a role in HBeAg clearance, which is known to suppress HBV replication and, to a lesser extent, in HBsAg clearance in HBV carriers. Although the HBeAg +/HBsAg + ratio in anti-HDV+ subjects was lower than in anti-HDV-subjects, there was no statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prevalence of HBV and HDV infection as well as risk factors for parenteral transmission were investigated in a prison with 680 intravenous drug abusers. Although HDV superinfection has generally been observed to have deleterious effects on HBsAg carriers and it results in progressive and refractory courses [Smedile et al, 1982;Rizzetto et al, 1983;Hadler et al, 19841, uneventful or even self-lim- ited clinical courses have also been reported [Chen et al, 1987a;Ichimura et al, 1988;Ambu et al, 19881. To address this, liver function tests were also studied. Subjects In August 27-29, 1986, 761 (99%) serum samples from 772 men were collected from a prison a t Yun-Lin County, located in the central part of Taiwan.…”
Section: Introductionmentioning
confidence: 99%